How to Incorporate Accessibility to Design Principles for IS Artefacts? - Mäkipää, Juho-Pekka; Vartiainen, Tero (University of Maribor, 2023)
Design principles are used to specify design knowledge and describe the aim of artefact instantiation. Accessibility research aims to create artefacts that can be used by all users. However, schemes for design principles lack the tools to define accessibility explicitly. This study proposes extensions to scheme design principles for accessibility-related design science research. We draw accessibility domain-specific characteristics from the literature to include accessibility in design principles for Human-Computer Interaction (HCI) instantiations. We extended the components of design principles with the following attributes: HCI Artefact Features; Contextual factors; Computer Input Modalities; Computer Output Media; Human Sensory Perception; Human Cognition; Human Functional Operations. We devised a checklist for researchers to follow the variations in accessibility. The extensions are intended to foster researchers to incorporate accessibility in producing a more accurate formulation of design principles.
Keywords: design principles; design science research; IS artefacts; information systems; accessibility; fi=Tietojärjestelmätiede|en=Information Systems|